2019
DOI: 10.1007/s00330-019-06486-0
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ views on the implementation of artificial intelligence in radiology: development and validation of a standardized questionnaire

Abstract: Objectives The patients' view on the implementation of artificial intelligence (AI) in radiology is still mainly unexplored territory. The aim of this article is to develop and validate a standardized patient questionnaire on the implementation of AI in radiology. Methods Six domains derived from a previous qualitative study were used to develop a questionnaire, and cognitive interviews were used as pretest method. One hundred fifty-five patients scheduled for CT, MRI, and/or conventional radiography filled ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(145 citation statements)
references
References 20 publications
6
138
1
Order By: Relevance
“…53 Issues raised by patients include distrust, lack of knowledge, a lack of personal interaction, questions about the efficacy of the AI algorithm, and the importance of being properly informed of its uses. 54 Similar relevant issues were identified by a computer science literature review 55 on human-AI interaction, such as task allocation, lack of knowledge and/or trust, incorrect use due to confusion, and integration issues due to a potentially radically different work practice.…”
Section: Discussionmentioning
confidence: 83%
“…53 Issues raised by patients include distrust, lack of knowledge, a lack of personal interaction, questions about the efficacy of the AI algorithm, and the importance of being properly informed of its uses. 54 Similar relevant issues were identified by a computer science literature review 55 on human-AI interaction, such as task allocation, lack of knowledge and/or trust, incorrect use due to confusion, and integration issues due to a potentially radically different work practice.…”
Section: Discussionmentioning
confidence: 83%
“…16 Further, most published studies have focused on computer vision health AI applications in radiology and dermatology, which represent only a small fraction of the potential applications of AI in health. [23][24][25] Additionally, there is a need to understand public perspectives versus patient perspectives, because health AI research may rely on large datasets that include information about people who do not have health conditions and/or do not stand to benefit directly from the research. Accordingly, the objective of this study was to learn more about how members of the general public perceive health data being used for AI research.…”
Section: Open Accessmentioning
confidence: 99%
“…Tran, et al found that after direct experience with medical AI patients saw AI as a great opportunity for improvement in medicine; it would improve follow-up care, reduce burdens of treatments and help facilitate physicians' work [4]. Patients are reluctant to rely on AI-supported medical care even when this kind of technology is proven to outperform human doctors [4][5][6][7]. Ongena, et al recommended future studies to help doctors and healthcare systems to identify ways to help patients overcome the distrust of AI technology [6].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Patients are reluctant to rely on AI-supported medical care even when this kind of technology is proven to outperform human doctors [4][5][6][7]. Ongena, et al recommended future studies to help doctors and healthcare systems to identify ways to help patients overcome the distrust of AI technology [6]. Recognizing factors that contribute to patients' distrust will benefit patients and facilitate implementation of medical AI patient protocols for doctors, healthcare facilities and AI researchers.…”
Section: Literature Reviewmentioning
confidence: 99%